2011
DOI: 10.1593/neo.11260
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factor 4 Inhibits Tumorigenic Progression and Metastasis in a Mouse Model of Breast Cancer

Abstract: Krüppel-like factor 4 (KLF4) is a zinc finger transcription factor that functions as an oncogene or tumor suppressor in a highly tissue-specific cell-dependent manner. However, its precise role in breast cancer and metastasis remains unclear. Here, we show that transient adenoviral expression of KLF4 in the 4T1 orthotopic mammary cancer model significantly attenuated primary tumor growth as well as micrometastases to the lungs and liver. These results can be attributed, in part, to decreased proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 46 publications
10
88
1
Order By: Relevance
“…Thus, in invasive ductal breast carcinoma increased KLF4 nuclear staining is associated with poor prognosis [14]. However, KLF4 was recently shown to inhibit tumor progression in a xenograft animal model [15] and EMT in vitro [11]. KLF4 accordingly up-regulates E-cadherin expression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in invasive ductal breast carcinoma increased KLF4 nuclear staining is associated with poor prognosis [14]. However, KLF4 was recently shown to inhibit tumor progression in a xenograft animal model [15] and EMT in vitro [11]. KLF4 accordingly up-regulates E-cadherin expression.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the inhibitory effects of the KLF4 gene on breast cancer progression, Yori et al (15) revealed that KLF4 overexpression in human breast cancer MDA-MB-231 cells upregulated the protein and mRNA levels of E-cadherin, which were decreased by interfering with its expression. Yori et al (25) also reported that KLF4 inhibited the invasion and distal metastasis of breast cancer by suppressing epithelial-mesenchymal transition.…”
Section: Discussionmentioning
confidence: 96%
“…Downregulation of KLF4 decreases tumor formation in vivo, while overexpression of KLF4 increases CSC population (Yu et al, 2011). Therefore, it seems that KLF4 can suppress the EMT process and inhibit metastasis in breast cancer cells (Yori et al, 2010(Yori et al, , 2011, however, it can also induce CSC-like properties to promote metastasis and invasion. In lung cancer cell lines, inhibition of KLF4 by Numb-like protein (NUMBL) maintains progenitor-like cells (Vaira et al, 2013).…”
Section: Role Of Klf4 In Cscsmentioning
confidence: 99%